Literatur Review: Efek Samping Penggunaan Obat Hipertensi - Sekar Anastry Putri; Dwi Aulia Ramdini; Afriyani; M. Fitra Wardhana (Medula, 2023)
Hypertension is a major risk factor for cardiovascular disease. Hypertension also has another term, namely "silent killer" which can be interpreted that it is not uncommon for people with hypertension to find it difficult to realize or even not to feel the warning symptoms of their disease. Treatment for hypertensive patients is a treatment therapy that needs to be done in the long term or for life. The problem often occurs in the treatment of chronic diseases that require long-term treatment such as hypertension because there are still many patients who do not comply with the treatment therapy they should be undergoing. One of the causes of non-compliance is the presence of patients who experience side effects from treatment. A drug side effect is an unwanted event and is detrimental to the patient as a result of drug use. Side effects that often occur in amlodipine therapy are: palpitations, flushing, ankle edema, hypotension, headache and nausea. Captropil can cause hyperkalemia and dry cough. Side effects of beta blockers that can occur are insomnia, hallucinations and depression. Clonidine can cause side effects such as dry mouth with symptoms of dry and cracked lips. Treatment with hydrochlorothiazide generally causes complaints related to side effects of the drug including frequent urination, feeling weak and wanting to faint, and abnormal heart rate. The use of diuretics can cause increased levels of uric acid or hyperuricemia resulting in deposition of uric acid, acute arthritis, nephrolithiasis.